How spatiotemporal dynamics can enhance ecosystem resilience - Pablo Moreno-Spiegelberg; Max Rietkerk; Damià Gomila (Proceedings of the National Academy of Sciences, 2025)
We study how self-organization in systems showing complex spatiotemporal dynamics can increase ecosystem resilience. We consider a general simple model that includes positive feedback as well as negative feedback mediated by an inhibitor. We apply this model to Posidonia oceanica meadows, where positive and negative feedbacks are well documented, and there is empirical evidence of the role of sulfide accumulation, toxic for the plant, in driving complex spatiotemporal dynamics. We describe a progressive transition from homogeneous meadows to extinction through dynamical regimes that allow the ecosystem to avoid the typical ecological tipping points of homogeneous vegetation covers. A predictable sequence of distinct dynamical regimes is observed as mortality is continuously increased: turbulent regimes, formation of spirals and wave trains, and isolated traveling pulses or expanding rings, the latter being a harbinger of ecosystem collapse, however far beyond the tipping point of the homogeneous cover. The model used in this paper is general, and the results can be applied to other plant–soil spatially extended systems, regardless of the mechanisms behind negative and positive feedbacks.